Pengembangan Wisata Budaya Wayang Wong di Desa Wisata JSPB Songgo Langit Mangunan - Tanto Lailam; Awang Daru Murti; Ani Yunita (IKIP PGRI Bojonegoro, 2021)
The community empowerment program is a “Program Pemberdayaan Desa Mitra” with the theme of Mangunan Village tourism for good tourism, competitive and cultured. The program focused on the development of traditional performance (puppet) / wayang wong as cultural tourism which is integrated with the natural exploration of Bowongan Agricultural rice fields, bowongan peaks, watu pipisan and traditional culinary